A novel tool to quantify in vivo lumbar spine kinematics and 3D intervertebral disc strains using clinical MRI. (April 2023) - Tavana, S.; Davis, B.; Canali, I.; Scott, K.; Leong, J.J.H.; Freedman, B.A.; Newell, N.
Abstract: Medical imaging modalities that calculate tissue morphology alone cannot provide direct information regarding the mechanical behaviour of load-bearing musculoskeletal organs. Accurate in vivo measurement of spine kinematics and intervertebral disc (IVD) strains can provide important information regarding the mechanical behaviour of the spine, help to investigate the effects of injuries on the mechanics of the spine, and assess the effectiveness of treatments. Additionally, strains can serve as a functional biomechanical marker for detecting normal and pathologic tissues. We hypothesised that combining digital volume correlation (DVC) with 3T clinical MRI can provide direct information regarding the mechanics of the spine. Here, we have developed a novel non-invasive tool for in vivo displacement and strain measurement within the human lumbar spine and we used this tool to calculate lumbar kinematics and IVD strains in six healthy subjects during lumbar extension. The proposed tool enabled spine kinematics and IVD strains to be measured with errors that did not exceed 0.17 mm and 0.5%, respectively. The findings of the kinematics study identified that during extension the lumbar spine of healthy subjects experiences total 3D translations ranging from 1 mm to 4.5 mm for different vertebral levels. The findings of strain analysis identified that the average of the maximum tensile, compressive, and shear strains for different lumbar levels during extension ranged from 3.5% to 7.2%. This tool can provide base-line data that can be used to describe the mechanical environment of healthy lumbar spine, which can help clinicians manage preventative treatments, define patient-specific treatments, and to monitor the effectiveness of surgical and non-surgical interventions. Graphical abstract: Image 1 Highlights: An in-vivo tool for spinal disc displacement and strain measurements was developed. Methodological parameters and MRI sequences were optimised. Lumbar kinematics and disc strains were measured in six volunteers during extension. Using the tool, the mechanics of healthy lumbar spines can be quantified. Clinicians can use the tool to inform preventative and patient-specific treatments.